Why do the poor receive poor services? - Keefer, Philip; Khemani, Stuti (2004)
India exhibits a large reliance on targeted transfer payments and subsidies, and significant under provision of social services such as education. These are puzzling outcomes because the poor in India, who vote in large numbers, would benefit most from more of the latter and less of the former. This paper argues that inadequate social services and excessive targeted transfers can be explained as a consequence of the incomplete information of voters, lack of credibility of political promises, and social polarisation. - Reproduced.
Keywords: Poverty - India; Social services - India; Social services